DO SOCIAL MEDIA CONTENT MARKETING AND CUSTOMER ENGAGEMENT INFLUENCE PURCHASE INTENTION? EVIDENCE FROM INDONESIAN CUSTOMERS - Endang Sulistya Rini (JURNAL DIMENSI, 2022)
Content marketing emerged as a popular strategic marketing initiative for the digitization of information, which has undergone dramatic changes. The emergence of social media has become a driving force behind change in the field of marketing, especially in relation to connecting with customers and engaging them in the activities of creating or sharing content and business transactions. Therefore, this research aims to reveal the influence of content marketing and customer engagement in social media on purchase intention. This research uses a quantitative- deductive approach and uses the survey method to collect data. There is empirical evidence that consumer engagement mediates the relationship between content marketing and purchase intention. Other empirical analysis results are expressed in the discussion section.